Gut Dysbiosis Thwarts the Efficacy of Vaccine Against Mycobacterium tuberculosis - Nadeem, Sajid; Maurya, Sudeep K.; Das, Deepjyoti K.; Khan, Nargis; Agrewala, Javed N. (Frontiers in Immunology, 2020)
The generation of enduring protective immunity by vaccines is of utmost importance. Intriguingly, there is considerable variation in the efficacy of vaccines amongst individuals. Emerging evidence indicate that native microbial squad of gastrointestinal tract plays a vital role in maintaining host homeostasis and immunity. Since gut microbiome is also extremely variable between individuals, we speculate that it might impact individual’s response to vaccines. Consequently, we administered broad spectrum antibiotics cocktail to induce gut dysbiosis and monitored its impact on the generation of long-lasting memory T cells and thereby BCG vaccine efficacy. Interestingly, gut dysbiosis significantly decreased the activation of CD4 T cells and CD8 T cells. Further, there was decline in the frequency of memory CD4 T cells and CD8 T cells in lungs and secondary lymphoid organs of the vaccinated animals. Moreover, it dampened the IFN-γ and TNF-α secretion and proliferation of Mtb-specific T cells. Most importantly, dysbiosis hampered Mtb clearance in vaccinated animals, as evidenced by increase in the colony forming units (CFUs) in lungs and spleen. We propose that alteration of gut microbiota can be one of the major factors responsible for variable efficacy of TB vaccines across the world.